Universal Jurisdiction as a Mechanism for the Enforcement of International Humanitarian Law (Journal of Human Sciences, 2026)
This research examines the principle of universal jurisdiction as one of the most significant developments in the structure of international criminal and humanitarian law. It represents a legal mechanism that allows states to exercise jurisdiction over serious international crimes — such as crimes against humanity, war crimes, and genocide — regardless of where they were committed or the nationality of the perpetrators or victims. The study highlights how this principle has strengthened the enforcement of international humanitarian law and contributed to preventing impunity by extending justice beyond territorial boundaries toward a universal human dimension. It further analyzes the legal foundations of this principle as established in international conventions, starting with the 1949 Geneva Conventions, the 1954 Hague Convention, and the 1984 Convention against Torture. The research also explores its implementation mechanisms through both international and national judicial systems. Moreover, it addresses the key challenges that hinder its practical application, particularly issues related to state sovereignty, immunities, and weak international cooperation. Finally, the study proposes measures to enhance the effectiveness of universal jurisdiction in achieving international justice and ensuring complementarity between national and international courts in holding perpetrators of serious international crimes accountable